Transformasi Pemahaman Hadits Pernikahan Dini dalam Perspektif Manajemen Pendidikan Keluarga Islam - Maulana Malik Ibrohim; Nasrulloh (Al-Kindi, 2026)
Early marriage in Indonesia creates tension between positive law (Law No. 16 of 2019) and the theological legitimacy believed by some communities, which rests upon a textual understanding of the hadith regarding Aisyah's marriage. This study aims to analyze the paradigm shift in hadith interpretation from a textual to a contextual approach and evaluate its relevance to state policies and Islamic family education management. The method utilized is qualitative library research with a contemporary Ma'anil Hadis and Maqashid al-Shariah approach. The findings indicate a significant shift: from determining maturity based on bulugh (biological signs) towards emphasizing Substantive Maturity (rusyd). The hadith concerning ba'ah (ability) is reinterpreted as a multidimensional competence, including mental, emotional, and managerial readiness. Juridically, state policies, such as providing marriage deferral incentives, gain syar'i legitimacy as they represent the Ulil Amri's efforts to prevent madharat (harm) and preserve hifz al-nasl (family resilience). In conclusion, the contextual understanding of hadith aligns with the objectives of Shariah and provides a theoretical foundation for Islamic Education Management to develop a pre-marital education curriculum based on holistic maturity.